2016
DOI: 10.5194/gh-71-121-2016
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and solutions for long-term permafrost borehole temperature monitoring and data interpretation

Abstract: Abstract. Long-term borehole temperature monitoring in mountain permafrost environments is challenging under the hostile conditions reigning in alpine environments. On the basis of data measured in the SLF borehole network we show three situations where ground temperature data should be interpreted with caution. (i) Thermistors have the tendency to drift, particularly if exposed to moisture or mechanical strain. This induces apparent warming or cooling, which can be difficult to differentiate from real ground … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Meanwhile, we assume isotropic thermal properties, even though foliation and geological structure may result in anisotropic behavior. However, despite these simplifications and assumptions, our modeled temperature field matches local observations in a borehole (Luethi & Phillips, ), and the predicted amplitudes of seasonal surface displacements fit comfortably within the range of past field measurements (Bakun‐Mazor et al, ; Gischig et al, ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Meanwhile, we assume isotropic thermal properties, even though foliation and geological structure may result in anisotropic behavior. However, despite these simplifications and assumptions, our modeled temperature field matches local observations in a borehole (Luethi & Phillips, ), and the predicted amplitudes of seasonal surface displacements fit comfortably within the range of past field measurements (Bakun‐Mazor et al, ; Gischig et al, ).…”
Section: Discussionsupporting
confidence: 71%
“…Gischig et al, 2011b;Moore et al, 2011). The modeled depth of the thermally active layer matches long-term temperature measurements from a nearby 10-m deep borehole at Eggishorn (Luethi & Phillips, 2016). Our thermal properties and model boundary conditions yield a geothermal gradient of Journal of Geophysical Research: Earth Surface ~21°C km À1 (see Figure 5), similar to a reported geothermal gradient of 23°C km À1 in the Aar massif by Rybach & Pfister (1994).…”
Section: Model Approach and Inputssupporting
confidence: 74%
“…According to Holmberg et al [1997], drift is a temporal shift of sensor response under constant physical and chemical conditions. These conditions are typically induced by water damage to the sensors or water fluxes within the ground, which could affect the interpretation of data to be seen as measurement errors [Luethi and Phillips 2016]. Luethi and Phillips [2016] discussed the challenges and solutions for long-term permafrost borehole temperature monitoring and data interpretation.…”
Section: Sensor Drift and Calibrationmentioning
confidence: 99%
“…These conditions are typically induced by water damage to the sensors or water fluxes within the ground, which could affect the interpretation of data to be seen as measurement errors [Luethi and Phillips 2016]. Luethi and Phillips [2016] discussed the challenges and solutions for long-term permafrost borehole temperature monitoring and data interpretation. Utilizing WSN for WQM requires sensors to detect certain parameters in real time, which comes with technology-related limitations known as sensor drift.…”
Section: Sensor Drift and Calibrationmentioning
confidence: 99%
“…To the best of our knowledge, in the entire European Alps only the Aiguille du Midi site (Chamonix, France, 3842 m a.s.l.) (Ravanel and Deline, 2011;Magnin et al, 2015), the permafrost borehole on the Jungfraujoch (Grindelwald, Switzerland, 3700 m a.s.l.) (Wegmann, 1997(Wegmann, , 1998Noetzli et al, 2019), the geothermal profiles on Stockhorn (Gruber et al, 2004c) and two simple ground surface temperature sensors located on the summit of the Matterhorn (4478 m a.s.l.)…”
Section: Introductionmentioning
confidence: 99%